PENGAMBILAN KEPUTUSAN KEUANGAN DENGAN PENDEKATAN ANALISIS RASIO KEUANGAN PADA RSUD CIAWI KABUPATEN BOGOR - Susandra, Farizka; Gandara, Itang (Universitas Djuanda, 2017)
Research comparative descriptive is a study to analyze the financial ratios as a financial decision on hospitals Ciawi Bogor Regency using ratio analysis, liquidity, solvency, activity, profitability, and 7 indicators of financial ratios and other aspects of compliance management BLUD in assessing the financial performance of hospitals ie cash ratio, current ratio, accounts receivable collection period, fixed asset turnover, return for an investment / on assets, return for equity and operating income over operating costs. The results showed that the analysis of the financial performance of Bogor Regency Hospital Ciawi based analysis of the liquidity ratio, solvency, activity and profitability showed good performance and is based on financial performance indicators of hospitals, the financial performance of the Bogor Regency Ciawi Hospital in 2011-2014 included in honors / healthy. Financial decision that should be done is to maintain the level of liquidity, solvency, activity. For the assessment of the level of profitability is still low can be done through the improvement of service in order to revenues from services is increasing as the improvement of facilities and infrastructure of hospitals, increased utilization of asset value, and the increase in the number of employees in the service and cost control services and general administrative expenses are still high and if possible there are adjustments to tariffs.Keywords: Liquidity, Solvency, activity, profitability, and financial decision making.